Accelerated Degradation Test of Lyophilized Recombinant Tissue Factor-Liposome Preparations - van den Besselaar, A M H P; Witteveen, E; Mansfeld, Schaefer-van H; Meeuwisse-Braun, J; Strebus, A (Thrombosis and Haemostasis, 1995)
Accelerated degradation experiments were performed to assess the heat stability of lyophilized recombinant tissue factor-liposome preparations from two different manufacturers. When stored at 4° C, these preparations did not show a significant change of the prothrombin time (PT). Two preparations (coded rTF-2 and rTF-a) showed a progressive prolongation of the PT on storage at 30° C, 37° C, and 44° C. The third preparation showed an initial decrease of the PT at 37° C and 44° C followed by a progressive prolongation. Although none of the three preparations was absolutely stable at 30° C, 37° C and 44° C, rTF-2 had the advantage that its PT-ratio (and hence its International Sensitivity Index) did not change under the conditions used in this study. The PT-ratio with a reference material for rabbit brain tissue factor (CRM149S) stored under similar conditions, did not change either.